2016
DOI: 10.3390/met6110260
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ultrasonic Treatment on the Solidification Microstructure of Die-Cast 35CrMo Steel

Abstract: Abstract:The effects of ultrasonic treatment (UST) on the solidification microstructure of a 35CrMo steel cast ingot were investigated. To avoid the erosion of a high-temperature melt, a T-shaped ultrasonic waveguide unit was used to introduce ultrasonic vibrations into a 35CrMo steel die casting melt. The experimental results show that the microstructure of the ingot was refined by ultrasonic treatment. While the microstructure of untreated 35CrMo steel is coarse dendritic grains, after the introduction of ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…The results have shown that ultrasonic vibration application during solidification of aluminum alloys is more efficient when the transition metals such as Zr and Ti are present in the alloy [23]. Different than extensively examined aluminum alloys, the effects of ultrasonic vibration on the microstructure and mechanical properties on Mg-8Li-3Al [24], AS41 [25], Al-4Mg [26] alloys and 35CrMo steel [27] were investigated. Researchers reported that the UST positively affected the microstructure of these materials [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…The results have shown that ultrasonic vibration application during solidification of aluminum alloys is more efficient when the transition metals such as Zr and Ti are present in the alloy [23]. Different than extensively examined aluminum alloys, the effects of ultrasonic vibration on the microstructure and mechanical properties on Mg-8Li-3Al [24], AS41 [25], Al-4Mg [26] alloys and 35CrMo steel [27] were investigated. Researchers reported that the UST positively affected the microstructure of these materials [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…In order to solve these problems, we successfully developed a kind of nanoceramic material that can effectively slow down the dissolution of sonotrode in steel melt, and we designed the T-shaped ultrasonic waveguide rod, which could successfully avoid the damage of the upward thermal radiation to the ultrasonic transducer [18,19]. In order to improve the performances of large-size cast ingot, we revised the sizes of ultrasonic waveguide rod and changed T-shaped rod into L-shaped rod that can produce flexural vibration and strengthen vibration's radial propagation in large-size steel melt, while the traditional straight ultrasonic waveguide rod produces longitudinal vibration and makes it propagate along axis direction.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the ultrasonic transducer, connected with the traditional straight-rod titanium alloy wave guide rod, is directly above the high-temperature metal melt, and the melt produces direct high-temperature heat radiation to the ultrasonic transducer. This often leads to the detuning problem of an ultrasonic vibration system or even damage of the transducer during the casting process, so it is difficult to achieve long-term stable ultrasonic treatment [27,28]. In this work, to overcome these problems, a new L-shaped ceramic ultrasonic wave guide rod was designed to introduce ultrasonic bending vibration into 2A14 aluminum alloy melt.…”
mentioning
confidence: 99%